Challenges and Resilience of First-Year Chinese International Students on Academic Probation - Huang, Qi; Qin, Desiree Baolian; Liu, Jiayi; Park, Hye-Jin (Journal of International Students, 2023)
A substantial percentage of international students are placed on academic probation each year. This study explored the challenges and resilience characteristics of Chinese international students placed on academic probation in their first year of college. Semi-structured interviews were conducted with nine probationary Chinese international students, and the data were analyzed using a thematic analysis approach. The results indicated that challenges with daily routine, reduced adult supervision, inadequate academic preparation, and limited participation in the application process were the main factors that contributed to their academic probation. Proactivity, independence, and flexible thinking were important resilience characteristics that may have helped students cope positively with stresses relating to academic probation. Targeted institutional support could be strengthened. Implications, limitations, and suggestions for future research are also discussed.